A randomized, controlled, 12-month trial on the effects of an interdisciplinary treatment approach in ESRD patients: study protocol of the smart and fit for kidney transplantation trial (S&F4KTx) - Helge Krusemark; Judith Kleemann; Julian Weigand; Dennis Kannenkeril; Katharina Heller; Tobias Hepp; Marc Albersmeyer; Doris Gerbig; Mario Schiffer (Trials)
Abstract Background A prolonged waiting time for a kidney transplant leads to a significant decline in the general health status of many patients with chronic kidney disease (CKD). This deterioration may cause these patients to be classified as unsuitable for transplantation during the waiting period owing to frailty, poor body composition, or the development of new comorbidities. Studies have shown that physical exercise and tailored nutrition can maintain and improve physical performance and overall health status. Methods This study is a 1:1 controlled, randomized trial. The control group will receive standard care along with an app designed for dialysis patients, which provides information on topics such as nutrition, vital signs, blood parameters, and details about their condition. In addition, the intervention group will receive individualized nutritional and exercise recommendations, along with a 3-week inpatient rehabilitation program. At 0, 6, and 12 months, body composition (body mass index, skeletal muscle mass, body fat mass, and waist circumference) and physical performance (6-min walk test, timed up and go test, sit-to-stand test, one-legged stance test, stair climbing test, and frailty), blood values (e.g., potassium and phosphate), and quality of life (KDQOL) will be evaluated. Bone density (tibia and radius) will be measured at 0 and 12 months. Discussion Studies have demonstrated that physical activity and tailored nutrition have positive effects on the general health of dialysis patients. However, pretransplantation preparation programs (prehabilitation) aimed at preserving transplant eligibility have not yet been evaluated. This study aims to address this gap by investigating a potential care program for patients on the transplant waiting list. Trial registration ClinicalTrials.gov NCT06040281. Registered on September 15, 2023. Trials status Protocol version number: 4 (30.07.2025). Recruitment start: 18.09.2023. Recruitment completed: 30.06.2025.